الإشراف القضائى على انتخابات الإدارة المحلية فى ظل الإصلاحات السياسية فى سورية - ونوس، وسام; الأحمد، نجم; عمار، سنان (جامعة البعث, 2019)
To ensure that any genuine democratic system and ensure the legitimacy and transparency of the electoral process requires that the state acts to ensure the rule of freedom of people to choose its representative through fair and periodic elections, which are held on the basis of secret ballot and on an equal basis , and this principle can only be achieved when the state establishes the suitable investigative mechanisms. Among these mechanisms which are brought by the Syrian legislator in light of the international and regional changes and in light of the political reforms in Syria. The principle of judicial supervision, which was crystallized in the General Elections Law No.5 dated 24/03/2014 issued by legislative decree No. 101 dated 03/08/2011. The experience of the local administrations elections that took place on 12/12/2011 was a realistic reflection of the electoral process, which was strengthened more strongly after issuing the general election law and the promotion of the idea of political pluralism, and embodiment the role of the higher committee for elections and sub-judicial committees in supervising the conduct of the electoral process and the success of the election.
لضمان قيام أي نظام ديموقراطي حقيقي وضمان شرعية وشفافية العملية الانتخابية، يقتضي أن تعمل الدولة على ضمان قاعدة حرية الشعب في اختياره لممثلية عن طريق انتخابات نزيهة ودورية، تجري على أساس الاقتراع السري وعلى قدم المساواة بين الجميع، ولا يتحقق هذا المبدأ إلا بقيام الدولة بوضع الآليات الكفيلة الحقيقية. ومن هذه الآليات التي جاء بها المشرع السوري في ظل المتغيرات الدولية واللإقليمية وفي ظل الإصلاحات السياسية التي شهدتها سورية؛ مبدأ الإشراف القضائي الذي تبلور في قانون الانتخابات العامة رقم /5/ تاريخ 24/3/2014 الصادر بموجب المرسوم التشريعي رقم (101) تاريخ 3/8/2011. وكانت تجربة انتخابات الإدارة المحلية التي جرت بتاريخ 12/12/2011 انعكاسا واقعيا للعملية الانتخابية التي تعززت بشكل أقوي بعد صدور قانون الانتخابات العامة وتعزيز فكرة التعددية السياسية، وتجسيد دور اللجنة العليا للانتخاب واللجان القضائية الفرعية في الإشراف على سير العملية الانتخابية ونجاح الاستحقاق الانتخابي.
Keywords: الإشراف القضائى -- العملية الانتخابية -- الاستحقاق الانتخابى -- الاقتراع السرى -- انتخابات الإدارة المحلية -- سورية